FACTORS INFLUENCING PERCEIVED KNOWLEDGE OF THERMOSTABLE NEWCASTLE DISEASE VACCINE AMONG LOCAL CHICKEN FARMERS OF PLATEAU STATE, NIGERIA - Apeh, D.; Bala, A. H.; Jibril, S.A.; Garba, M.; Haruna, I.M.; Olabode, M.P. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the factors influencing the perceived knowledge of thermostable Newcastle disease vaccine among local chicken farmers in Plateau State, Nigeria. Multi-stage sampling technique was used in selecting; 369 farmers. Data were collected through the use of a structured questionnaire and analysed using descriptive and inferential statistics. The results indicated that the mean age were 43 years, 8 persons; and 13 years, respectively. The study revealed a predominance of female respondents (58.8%), and majority (86.4%) were married. Notably, 78% of the farmers reported no interaction with agricultural extension agents, and 87% were not members of any cooperative society. Only 24.4% obtained information about the vaccine from Community Animal Health Workers (CAHWs), and a most (91%) had no access to credit. The results also indicated that 47.7% of respondents had low knowledge of the vaccine, while 55% lacked access to the technology. The results of logistic regression model revealed that sex (P<0.01), age (P<0.01), education (P<0.01), household size (P<0.10), flock size (P<0.01), and farming experience (P<0.05) were the factors influencing perceived knowledge and practices of thermostable Newcastle disease vaccine among local chicken farmers in the study area. The study concluded that sex, age, education, household size, flock size and farming experience were the factors influencing the perceived knowledge of thermostable Newcastle disease vaccine among local chicken farmers. Based on the findings, we recommend enhancing farmer capacity through targeted training and community demonstrations tailored to literacy levels, gender, and age, thereby addressing demographic variations that impact vaccine adoption.